Kepuasan Kerja; Harapan dan Tantangan Bagi Konselor - Asmidir Ilyas (Fakultas Ilmu Pendidikan UNP, 2017)
Based on the result of research, known that employees has job satisfaction level that is low enough in consequence of low job satisfaction level. Work satisfaction is one of important factor to gaining optimum work result. Target demand of working without support from characteristic condition will result overload work stress to the worker that in the end will making work stress disruption that impacted to work satisfaction. According to House (1981) in Deeter and Ramsey (1997), someone who has better social support so he will also better to reducing stress that occurs in their work. So that if a worker who has a higher social support so he could better in managing work stress that experienced and looking work stress with different way that able to giving a positive impact to the worker. This condition become the expection and apportunity by counselor profesion and sollution employed problem.